Arsitektur Tradisional Rumah Adat Sapo Jojong Suku Pakpak di Kabupaten Pakpak Bharat - Nurmalasari Tumangger; Armelia Dafrina; Fidyati Fidyati; Diana Khairani Sofyan (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
Characteristics of the Sapo Jojong Traditional House in Penanggalan Binanga Boang Village, has the characteristics of a traditional Pakpak house which is considered quite representative as one of the traditional houses in Pakpak Bharat Regency. The aim of this research is to identify the historical development and architectural aspects of the Sapo Jojong traditional house. Some of the architectural aspects identified include: the spatial system (patterns of spatial relationships, orientation, and hierarchy), the physical system (physical form, space dividers, and materials), and the model system (roofs, columns, openings, ornaments/decoration). The method used in the research on the architectural characteristics of the Sapo Jojong traditional house is a survey method (direct observation) conducted in March-April 2023. Starting with the initial data collection followed by semi-structured interviews and conducting field observations, then the data is analyzed using qualitative descriptive methods.The results of this research show the architectural development of the Pakpak tribe and the characteristics of Sapo Jojong which can be seen from the identification of the spatial, physical, and model systems.